2022
DOI: 10.3389/fimmu.2022.962669
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1+ neutrophils as novel biomarkers for stage IV melanoma patients treated with nivolumab

Abstract: Melanoma displays a rising incidence, and the mortality associated with metastatic form remains high. Monoclonal antibodies that block programmed death (PD-1) and PD Ligand 1 (PD-L1) network have revolutionized the history of metastatic disease. PD-L1 is expressed on several immune cells and can be also expressed on human neutrophils (PMNs). The role of peripheral blood PMNs as predictive biomarkers in anti-PD-1 therapy of melanoma is largely unknown. In this study, we aimed to determine activation status and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…In humans, the circulating neutrophil-to-lymphocyte ratio (NLR) has been used as a prognostic biomarker for melanoma [ 35 , 36 ], although these findings have some limitations due to PMN heterogeneity [ 37 ]. We demonstrated that peripheral blood PD-L1 + PMN frequency predicts patient prognosis and response to the anti-PD-1 agent nivolumab in patients with stage IV BRAF wild-type melanoma [ 11 ]. To go deeper inside the mechanisms linking melanoma cells and PMNs, we investigated the cross talk between melanoma cell lines and human PMNs purified from peripheral blood of healthy donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the circulating neutrophil-to-lymphocyte ratio (NLR) has been used as a prognostic biomarker for melanoma [ 35 , 36 ], although these findings have some limitations due to PMN heterogeneity [ 37 ]. We demonstrated that peripheral blood PD-L1 + PMN frequency predicts patient prognosis and response to the anti-PD-1 agent nivolumab in patients with stage IV BRAF wild-type melanoma [ 11 ]. To go deeper inside the mechanisms linking melanoma cells and PMNs, we investigated the cross talk between melanoma cell lines and human PMNs purified from peripheral blood of healthy donors.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 is also expressed on neutrophils and is associated with several diseases [ 8 10 ]. We recently demonstrated that peripheral blood PD-L1 + PMN frequency predicts patient prognosis and response to the anti-PD-1 agent nivolumab in patients with stage IV BRAF wild-type melanoma [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Six phenotypically distinct human blood neutrophil populations were identified. The proportion and function of neutrophil subsets were shown to be correlated with melanoma stage, and their changes would favor the differentiation of different melanoma stages 353,354 . The profound study of neutrophils has also given hope for the treatment of melanoma.…”
Section: Neutrophil Heterogeneity In Diseasesmentioning
confidence: 99%
“…The proportion and function of neutrophil subsets were shown to be correlated with melanoma stage, and their changes would favor the differentiation of different melanoma stages. 353 , 354 The profound study of neutrophils has also given hope for the treatment of melanoma. A recent study showed that neutrophils, especially TAN1, were isolated from mice underwent innate immune training by exposure to β‐glucan hold a stronger antitumor effect.…”
Section: Neutrophil Heterogeneity In Diseasesmentioning
confidence: 99%
“…In cancer patients receiving anti-PD-1/PD-L1 therapy, a high neutrophil-to-lymphocyte ratio (NLR) is thought to have prognostic and predictive value [ 286 , 287 , 288 , 289 , 290 , 291 ]. Furthermore, neutrophils expressing PD-L1 were linked to a poor prognosis in patients with advanced melanoma and are thought to be a novel biomarker in stage IV melanoma patients receiving anti-PD-1 immunotherapy [ 292 ]. In addition, in melanoma patients, a high NLR value was associated with anti-PD-1/PD-L1 treatment failure [ 293 ].…”
Section: Neutrophil In Cancer Therapy: Potential Strategiesmentioning
confidence: 99%